High Waist to Height Ratio (WHtR) worsens inflammatory and adiposity profiles in adult women with abdominal obesity - Etika Ratna Noer; Sophia Rose; Alifia Mukti Fajrani; Devi Elvina Rachma; I Edward Kurnia Setiawan Limijadi; Deny Yudi Fitranti (Alma Ata University Press, 2022)
ABSTRACTBackground: Women gain weight more easily due to hormonal factors. Abdominal obesity is more at risk for metabolic disease than general obesity. Inflammation in the body is intimately linked to obesity. Adipocytokines are leptin and adiponectin, while IL-6 is a pro-inflammatory cytokine. These three biomarkers are frequently used to describe abdominal obesity individuals.Objective: This study aimed to analyze between Waist-to-Height Ratio (WHtR) with the inflammatory and adiposity profiles in adult women with abdominal obesity.Methods: This study was a cross-sectional research with a total of 88 adult women with abdominal obesity aged 25-45 years who work in the Diponegoro University area of Semarang. Samples were taken by consecutive sampling technique. A serum inflammation profile was measured using the enzyme-linked immunosorbent assay (ELISA) method.Results: The mean waist circumference of the research subjects was 93.82 ± 10.64. The mean WHtR, adiponectin, leptin and IL-6 were 0.61 ± 0.07; 14.15 ± 9.71; 4.64 ± 0.79; 6.49 ± 3.19. The results of the correlation test between WHtR with adiponectin, leptin and IL-6 were (r=-0.279; p=0.005), (r=0.233; p=0.029) and (r=0.271; p=0.011). Compared with anthropometric measurements using BMI, visceral fat, and WC, the WHtR was statistically higher (p<0.05).Conclusion: WHtR was significantly negatively correlated with adiponectin and positively correlated with leptin and IL-6 KEYWORD: Abdominal Obesity; WHtR; Adiponectin; Leptin; Interleukin 6 ABSTRAK Latar Belakang: Wanita lebih mudah mengalami kenaikan berat badan karena faktor hormonal. Obesitas abdominal lebih berisiko terkena penyakit metabolik daripada obesitas umum. Peradangan dalam tubuh berkaitan erat dengan obesitas. Adipositokin merupakan leptin dan adiponektin, sedangkan IL-6 adalah sitokin pro-inflamasi. Ketiga biomarker ini sering digunakan untuk menggambarkan individu dengan obesitas abdominal.Tujuan: Penelitian ini bertujuan untuk menganalisis hubungan antara Waist-to-Height Ratio (WHtR) dengan profil inflamasi dan adipositas pada wanita dewasa dengan obesitas abdominal.Metode: Penelitian ini merupakan penelitian cross sectional dengan jumlah 88 wanita dewasa dengan obesitas abdominal berusia 25-45 tahun yang bekerja di lingkungan Universitas Diponegoro Semarang. Sampel diambil dengan teknik consecutive sampling. Profil peradangan serum diukur menggunakan metode enzyme-linked immunosorbent assay (ELISA).Hasil: Rerata lingkar pinggang subjek penelitian adalah 93,82 ± 10,64. Rerata WHtR, adiponektin, leptin dan IL-6 adalah 0,61 ± 0,07; 14,15 ± 9,71; 4,64 ± 0,79; 6,49 ± 3,19. Hasil uji korelasi antara WHtR dengan adiponektin, leptin dan IL-6 adalah (r=-0,279; p=0,005), (r=0,233; p=0,029) dan (r=0,271; p=0,011). Dibandingkan dengan pengukuran antropometri menggunakan BMI, lemak visceral, dan WC, WHtR secara statistik lebih tinggi (p<0,05).Kesimpulan: WHtR secara signifikan berkorelasi negatif dengan adiponektin dan berkorelasi positif dengan leptin dan IL-6 KATA KUNCI: Obesitas Abdominal; WHtR; Adiponektin; Leptin; Interleukin 6